Qalʻah-yi Muʻallá kī jhalkiyāṉ - ʻArsh Taimūrī, 1921-1964 (SAMP early 20th-century Indian books project, 1937)
Palace life and customs in the Red Fort of Delhi during the last Moguls, chiefly 19th century.